Pengaruh Gaya Kepemimpinan KepalaSekolah, Manajemen Berbasis Sekolah (MBS) dan Iklim Organisasi terhadap kepuasan Kerja dan Kinerja Guru SMP di Wilayah Sub Rayon 04 Kabupaten Demak - - Sunarto; Djumadi Purwoatmodjo (Universitas Muria Kudus, 2011)
The purpose of this study is to analyze: (1) the influence of principal leadership style on teacher job satisfaction, (2) the influence of MBS on teacher working kepuassan, (3) the influence of organizational climate on the performance of teachers (4) the influence of principal leadership style on teacher performance , (5) the influence of MBS on teacher performance, (6) the influence of organizational climate on job satisfaction of teachers (7) the influence of teachers' job satisfaction on the performance of teachers. While the population of this research is junior high school teachers in Sub Rayon 04 Demak district, amounting to 395 teachers in 13 junior high schools, the sample of 100 people taken to calculate the population units. The instrument used was a questionnaire. Data analysis using SEM. The findings showed that (1) leadership has a significant influence on job satisfaction can be accepted, because the CR of 2.096 and significant at 0.036, a significant direct effect of 0.191. (2) MBS on job satisfaction is also acceptable because the CR of 3.206 and 0.001 significant, strong and direct effect of 0.318, (3) Organizational climate has a positive effect on job satisfaction can be accepted, because the CR of 2.750 and 0.006 significant and direct influence 0.261 strong. (4) leadership style has a significant influence on teachers' performance is acceptable, because the CR of 3.096 and 0.002 significant and direct effect of the strong 0.329. (5) MBS have significant and positive effect on job satisfaction can be accepted as equal to 2.162 and significant CR equal to 0.031, and a strong direct effect of 0.235. (6) organizational climate has no influence on teacher performance, as CR of 0.448 and significant at 0.654, and the direct effect is not significant at 0.044 and (7) job satisfaction has a positive and significant teacher performance is acceptable, because the CR of 3.183 and significant at 0.001, and a strong direct effect of 0.544.